The art of whimsical stitching : creative stitch techniques and inspiring projects - Sharpe, Joanne, 1959- (Interweave, 2016)
Paint, Stitch, Play! In The Art of Whimsical Stitching, bestselling author and teacher Joanne Sharpe shares her favorite, go-to methods for creating exuberant stitch art. If you're a sewer or quilter, you'll take your stitching in a new direction with paints, markers, and dyes. If you're a mixed-media artist, you'll learn to embellish your work with stitching. Follow step-by-step instructions and photos demonstrating a dozen inspiring techniques, including collage, stenciling, free-motion stitching, fused applique lettering, needle felting, doodle machine and hand embroidery, and more! Then, transform your custom fabric into playful pillows and bags, art quilts, journals, and other fun and funk-tional projects. Joanne's whimsical artwork and a "sketchbook" of designs you can adapt for your own work round out this colorful, inspirational guide.